The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s10643-008-0243-6
|View full text |Cite
|
Sign up to set email alerts
|

Community Childcare Providers’ Role in the Early Detection of Autism Spectrum Disorders

Abstract: The first few years of life represent a crucial period for optimal brain development for young children. Therefore, it is important to identify children at-risk for developmental delays, including autism spectrum disorders, at the earliest age possible. An argument for utilizing community childcare providers for universal developmental screening is presented along with suggestions for assessment tool selection and a model for developmental monitoring in community childcare settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 37 publications
0
28
0
1
Order By: Relevance
“…If intervention cannot begin in preschool years (i.e. to create important language and social-emotional experiences for the 4 child), this may result in missed opportunities for optimal brain development (Branson, Vigil, & Bingham, 2008). In addition, research has indicated that early diagnosis of the disorder can diminish familial stress, speed up referral to special educational programmes and influence family planning (Renty & Roeyers, 2006).…”
Section: Checklist For Early Signs Of Developmental Disorders (Cesdd)mentioning
confidence: 99%
See 1 more Smart Citation
“…If intervention cannot begin in preschool years (i.e. to create important language and social-emotional experiences for the 4 child), this may result in missed opportunities for optimal brain development (Branson, Vigil, & Bingham, 2008). In addition, research has indicated that early diagnosis of the disorder can diminish familial stress, speed up referral to special educational programmes and influence family planning (Renty & Roeyers, 2006).…”
Section: Checklist For Early Signs Of Developmental Disorders (Cesdd)mentioning
confidence: 99%
“…Others have also suggested the possible contribution of child care workers to the screening for ASD in young children (Branson et al, 2008).…”
Section: Screening For Asdmentioning
confidence: 99%
“…The American Academy of Pediatrics (AAP) has recommended universal ASD screening for all young children twice before their second birthday (27). However, in practice the AAP recommendations are not always followed and many children are not diagnosed before age five (28). The importance of early diagnosis is gaining momentum within the ASD community, especially as the understanding of how the disorder presents at younger ages grows (29).…”
Section: Diagnosismentioning
confidence: 99%
“…Although AAP guidelines recommend global screening twice before the second birthday, adherence appears to be lacking (28). The lack of adherence could be due to the subjectivity within screening, screening tools, or specific knowledge about ASD.…”
Section: Screening and Assessmentmentioning
confidence: 99%
“…Al igual que la sola participación de los padres no es suficiente, la opinión clínica de los pediatras sobre lo que observan acerca de un niño no puede considerarse tampoco la única fuente de información para determinar la sospecha de autismo de un niño, pues el comportamiento de éste en una consulta puede no ser representativo en absoluto de su comportamiento en el contexto habitual. Una manera de solucionar la necesidad de combinar estos dos informantes (padres y profesionales sanitarios) sería implantar los programas de cribado dentro de las escuelas infantiles, donde los educadores pueden observar y comparar con iguales el comportamiento de los niños durante largos periodos de tiempo pero esto sólo sería posible en lugares donde la mayor parte de los niños acudan a escuelas infantiles antes de los tres años, como, por ejemplo, demuestra el estudio realizado en Holanda (Branson, Vigil y Bingham, 2008;Dereu et al, 2010).…”
Section: La Participación Y Formación De Los Profesionalesunclassified